Measuring Instruments for Oxygen Concentration, Flow, Temperature, and Humidity in CPAP Equipped with Microcontroller Based External Data Storage - Wafa, Muhammad Ali; Assalim Tetra Putra, Moch. Prastawa; Wakidi, Levana Forra; Misra, Shubhrojit (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The recommended approach for addressing sleep apnea in infants involves the utilization of CPAP therapy. A pivotal component of CPAP therapy is the inclusion of a humidifier, which serves to counteract potential hazards by introducing humidified air. The purpose of this study was centered on developing a compact, portable model to assess temperature and humidity parameters in CPAP humidifiers. The method utilized was the pre-experimental One Group Post Test Design. The contribution of this research lies in its ability to measure temperature and humidity in the CPAP humidifier using the SHT30 sensor. The sensor readings were processed using the Arduino Mega 2560 Pro Mini microcontroller. The measurement data was presented on a 20x4 LCD screen and had the capability to be stored using an SD Card, alongside the inclusion of a buzzer indicator on the tool. The results demonstrated that the highest error value for the temperature parameter was 1.8%, while the lowest was 0.49%. The expected conclusion is that these findings can be implemented effectively to assist operators in recording, measuring, and monitoring temperature and humidity in CPAP humidifiers and to facilitate monitoring of sleep apnea treatment procedures.